Singapore : 2018 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Singapore. (IMF Staff Country Reports; Country Report ;, 2018)
Singapore's economy is on a strong cyclical upswing. Economic growth has recovered to a three-year high, led by externally-oriented sectors that benefitted from the synchronized global expansion. Economic momentum is becoming more broad-based, helping to reduce the labor market slack. Growth is expected at or above the potential rate in the near term, increasingly supported by domestic demand. Inflation is subdued but expected to rise modestly. The current account surplus, as a share of GDP, has remained large. Risks to the near-term outlook are broadly balanced and come mainly from external sources. Over the medium term, the structural transformation aimed to prepare Singapore for challenges from technological changes globally and population aging at home should help support higher productivity.